Everyday Suffocations, Smells and Sounds of Jung: Ethnography of Tear Gas in Downtown Srinagar (HIMALAYA, 2020)
This paper traces the insidious movement of tear gas shells from the site of jung (Kashmiri reference for stone-pelting, more directly referred to as Kanni Jung) to intimate spaces of homes, interrogating the world of unabated military violence in Downtown Srinagar. It delineates the sensate world of political conflict through the precarious social life of people and their multi-layered relationship with forms of military control, particularly tear gas shells1. In trying to capture the inbetween-ness of toxic tear gas—between striking protestors on the road and permeating inside homes, between explosion and diffusion— I ask: how does this “non-lethal” (Graham 2010: 244) chemical weapon affect the social world of people in Downtown? Can this gas, claiming to function specifically as a resistance-quelling weapon, differentiate neatly between ‘dangerous’ rioting bodies and bodies of civilians or between an azaadipasand2 (Kashmiri for pro-freedom) home and a non-azaadi3 pasand home? Borrowing from Bourdieu’s idea of the habitus (1990), the paper explicates that certain lived realities become embodiments and train the human body to preemptively act and respond in particular ways to everyday unfolding military violence. During the ethnographic fieldwork between 2015 and 2017 in Downtown Srinagar, I attempted to un-layer this sensory landscape of tear gas by exploring narratives of daem (Kashmiri for suffocation) that have acquired a routine texture in this toxic geography.